Latina Muslim Producers of Online and Literary Countermedia: A Case Study in Union City - New Jersey (American Journal of Islam and Society, 2019)
Since 9/11, US English and Spanish language media have reported on the rise in Latino/a conversion to Islam. Western(ized) media images I examined for this essay about Latinas converting to Islam raise suspicions overpossible forced conversions, brainwashing, or abuse. What is evident and salient in these media portrayals, whether deliberately or unintentionally created, are the binaries (Western vs. non-Western, Christian vs. Muslim, and Arab vs. Latino) that limit understandings of how these women are self-empowered and make choices for themselves in their everyday lives as Latina Muslim converts. In effect, Western imperial ideologies and discourses in these media portrayals reinforce and normalize rigid state identitarian notions of Christian/Catholic Latinas living in Union City, New Jersey, a traditionally Catholic/Christian-majority and urban  Cuban-majority/Latino immigrant enclave since the 1940s-1950s. Now more alarming is this post-9/11 moment when “the Latino American Dawah Organization (LADO) estimated that Latina women outnumbered their male counterparts and reached 60 per cent,” as part of a changing religious and ethnic demographic that includes Muslim Arab and South Asian populations amidst Latino/a populations. In my research, it soon became evident that a variety of media sources perceived Union City as a prime site of Latino/a Muslim conversion post-9/11. This essay offers a specific look at the way newsmedia has portrayed Latina Muslims in Union City and how the cultural productions of these women challenge simplistic and Islamophobic views of Latinas who have converted to Islam post-9/11.To download full review, click on PDF.